Development of Digital-based LKPD on Ecosystem Material - Trisno Widodo; Lelly Nur Rachmawati; Siti Nur Hasanah (CV. Edutechnium Indonesia, 2023)
This study aims to produce valid and practical digital-based LKPD on ecosystem material for junior high school students. This type of research is research and development. The media development design used is the 4-D (Four-D) model, namely define, design and development, and disseminate. However, this study was modified and limited to reaching the 3-D stage because the media developed was only to test the feasibility of the LKPD media. The subjects in this study were nine students of CLASS VII SMP. The instruments used include validation sheets and questionnaires. The study results show that the developed digital-based LKPD is valid as a student learning tool with an average percentage of 79.25%. The results of the student response questionnaire got 87.5% in the positive category. Using the developed LKPD can significantly increase students' interest in learning and improve learning outcomes.